Penerapan Manajemen Risiko Terintegrasi dalam Meminimalisir Kegagalan Program Kerja pada Himpunan Mahasiswa Manajemen - Putri, Deas Fazzirah; Rachmawati, Eva (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2025)
Integrated risk management plays a crucial role in addressing challenges and failures in organizational work programs. Through in-depth analysis of factors contributing to work program failures, this research highlights the importance of holistic risk identification, evaluation, and management. Integrated risk management provides a foundation for informed decision-making, enabling organizations to design effective mitigation strategies and making them more adaptive to environmental changes. In conclusion, this study asserts that integrated risk management is not merely an administrative aspect but an essential strategic element in achieving the long-term success and resilience of an organization.